Microalgae biotechnological application - Ліщук, А. В.; Васильченко, О. А.; Миненко, А. Б.; Касянівська, Е. С.; Кудас, В. Є. (Problems of Environmental Biotechnology, 2014)
The analysis of current research on the practical use of microalgae in biotechnology is conducted. The availability of microalgae as an object of biotechnology developments is assessed.